2017
DOI: 10.1007/s13744-017-0516-0
|View full text |Cite
|
Sign up to set email alerts
|

A Bird in the Hand Versus Two in the Bush? The Specialist Leafhopper Dalbulus maidis (Hemiptera: Cicadellidae) Does Not Discriminate Against Sub-optimal Host Plants (Zea spp.)

Abstract: The corn leafhopper [Dalbulus maidis (DeLong & Wolcott)] is a specialist on Zea (Poaceae) that coevolved with maize (Zea mays mays) and its teosinte (Zea spp.) relatives. This study tested the hypothesis that host acceptance by females varies among Zea hosts, and is correlated with variation in defensive levels across those hosts. Prior studies revealed differences in plant defenses among Zea hosts and corresponding differences in corn leafhopper performance. Thus, host acceptance was expected to be correlated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…In the present study, FAW neonate larvae exhibited greater ballooning activity than stemborers. Several studies suggested that in the cases where larval dispersal is limited, females select for high‐quality hosts (van Huis, 1981; Thompson, 1988; Roitberg et al, 1999; Zlotina et al, 1999; Gripenberg et al, 2010; Refsnider & Janzen, 2010; Bellota et al, 2017). Thus, the higher dispersal indicates that FAW is less involved in high‐quality host assessment and also more polyphagous than any of the stemborer species.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, FAW neonate larvae exhibited greater ballooning activity than stemborers. Several studies suggested that in the cases where larval dispersal is limited, females select for high‐quality hosts (van Huis, 1981; Thompson, 1988; Roitberg et al, 1999; Zlotina et al, 1999; Gripenberg et al, 2010; Refsnider & Janzen, 2010; Bellota et al, 2017). Thus, the higher dispersal indicates that FAW is less involved in high‐quality host assessment and also more polyphagous than any of the stemborer species.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the propensity for dispersal of neonate larvae may override the moth’s host choices and be adaptive, while female ovipositional preferences may be dynamic, i.e. shaped by variables other than their offspring’s performance, such as risk of parasitism or egg mortality, which may be high and differ among hosts [ 2 , 65 , 66 ]. For example, recent field studies showed that fall armyworm egg-stage mortality on maize was 73 to 81% [ 16 ], and that parasitism and predation risks of fall armyworm larvae were three- to four-fold higher on the maize wild ancestor Balsas teosinte ( Zea mays parviglumis ) compared to maize [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Females were removed after 5 d, and discarded, and seedlings were placed inside a cage, and leafhopper eggs allowed to hatch into nymphs. Fifteen days later, the number of nymphs per seedling was recorded, and the leaf section exposed to ovipositing females was excised from the seedling for subsequent recording of oviposition (below); the timing and spread of egg hatch and adult emergence times were known from prior studies (Dávila‐Flores et al ., ; Bellota et al ., ). Beginning at this time, cages were examined daily to record the emergence of adult leafhoppers.…”
Section: Methodsmentioning
confidence: 97%
“…Adults were removed as they appeared, and the time (days) to emergence and gender were recorded. The excised leaf section, exposed to oviposition, was stained per McBryde () to facilitate counting the number of eggs that were originally laid on a seedling; this procedure as applied to corn leafhopper was successfully used in prior studies (Bellota et al ., , ; Dávila‐Flores et al ., ). The following data were recorded for each seedling: numbers of eggs, nymphs, and adults, gender of adults, and development times (= the period from oviposition to emergence of adults).…”
Section: Methodsmentioning
confidence: 99%